2017
DOI: 10.18203/2349-3291.ijcp20171075
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum vitamin D levels and anemia in childhood pneumonia: a case control study from rural area

Abstract: INTRODUCTIONPneumonia remains the number one cause for under five deaths worldwide. Out of 6.3 million children dying before 5 years, 0.935 million patients die due to Pneumonia.1 Different approaches have been tried to reduce the morbidity and mortality due to pneumonia such as immunization, vitamin A supplementation and zinc supplementation. 3 The vitamin D converts immune response from TH1 to TH2 response. It also helps in rapid response at the cellular level. It helps in activation of macrophages. 4,5 It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
4
1
Order By: Relevance
“…Consistent with the present study, Kulkarni and Chougule in India found that the relationship between the mean weight of children with pneumonia and the control group was not significant (24). In addition, another study in India, consistent with the results of our study, showed that there was no significant relationship between vitamin D and the location of residence (city or village) (25).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with the present study, Kulkarni and Chougule in India found that the relationship between the mean weight of children with pneumonia and the control group was not significant (24). In addition, another study in India, consistent with the results of our study, showed that there was no significant relationship between vitamin D and the location of residence (city or village) (25).…”
Section: Discussionsupporting
confidence: 90%
“…The height of the case group was lower than the control group, but this difference was not significant. Unlike the present study, another survey demonstrated that the mean height of children with pneumonia was significantly shorter than the control group (24). Also, in a study by Wayse et al, a weak positive relationship was observed between short height and acute lower respiratory infection (ALRI), which may be due to some age mismatch in the case and control groups (26).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Thus, it was observed that children with vitamin D deficiency had more severe conditions. This was also observed in the study conducted by Kulkarni SP in 2017 19 .This study included the breast feeding status of the children. It was observed that there was not much difference in the vitamin D levels of children who were exclusively breastfed till 4 months of age and 6 months of age (Table 9, Figure 6) .…”
Section: Discussionsupporting
confidence: 57%
“…Vitamin D also appears to suppress the proliferation and production of T-helper 1 cytokines while promoting the proliferation and production of T-helper 2 cells and the production of regulatory T cells. Given the inflammatory effects of TNF-α, INF-γ, and other Th1 cytokines, optimizing vitamin D status, especially preventing deficiency, can prevent the dysregulation and circulation of more proinflammatory cytokines in infected individuals, which can play a role in decreasing the severity of the disease [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%